Zakat Accounting: Islamic Ethnomethodology Study - Thalib, Mohamad Anwar (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: This research problem revolves around the prevailing focus in zakat accounting studies, primarily on techniques and calculations, while neglecting the importance of local cultural values and religiosity. This study aims to reveal zakat accounting practices based on local cultural values and religiosity. Methodology/approach: The research employs a qualitative approach and utilizes two data collection methods, interviews and observations, involving three informants. Results: The findings reveal various zakat accounting practices, including the adjustment of zakat rates based on government decisions; straightforward zakat accounting records; the distribution of zakat to the poor, needy, converts, and zakat administrators; and the accountability of zakat funds communicated via mosque loudspeakers. These practices are deeply intertwined with local cultural values, emphasizing honesty and trustworthiness. Limitations: The limitations of this research are that the research informants have yet to present information from religious leaders regarding zakat accounting practices. Contribution: The theoretical implication lies in the potential integration of religious values, such as trustworthiness and honesty, into zakat accounting, facilitating the development of guidelines and standards that resonate with spiritual and cultural values and align organizations with their religious principles. Practically, this may create opportunities for developing zakat-based financial instruments tailored to specific cultural and spiritual contexts.